Possible Role of Nutritional Priming for Early Salt and Drought Stress Responses in Medicago truncatula - Staudinger, Christiana; Mehmeti, Vlora; Turetschek, Reinhard; Lyon, David; Egelhofer, Volker; Wienkoop, Stefanie (Frontiers in Plant Science, 2012)
Most legume species establish a symbiotic association with soil bacteria. The plant accommodates the differentiated rhizobia in specialized organs, the root nodules. In this environment, the microsymbiont reduces atmospheric nitrogen (N) making it available for plant metabolism. Symbiotic N fixation is driven by the respiration of the host photosynthates and thus constitutes an additional carbon sink for the plant. Molecular phenotypes of symbiotic and non-symbiotic M. truncatula are identified. The implication of nodule symbiosis on plant abiotic stress response mechanisms is not well understood. In this study, we exposed nodulated and non-symbiotic N fertilized plants to salt and drought conditions. We assessed the stress effects with proteomic and metabolomic methods and found a nutritionally regulated phenotypic plasticity pivotal for a differential stress adjustment strategy.